2021
DOI: 10.1055/s-0040-1722283
|View full text |Cite
|
Sign up to set email alerts
|

Merlin-Deficient Schwann Cells Are More Susceptible to Radiation Injury than Normal Schwann Cells In Vitro

Abstract: Objectives Vestibular schwannomas (VS) are intracranial tumors, which are caused by NF2 gene mutations that lead to loss of merlin protein. A treatment for VS is stereotactic radiosurgery, a form of radiation. To better understand the radiobiology of VS and radiation toxicity to adjacent structures, our main objectives were (1) investigate effects of single fraction (SF) radiation on viability, cytotoxicity, and apoptosis in normal Schwann cells (SCs) and merlin-deficient Schwann cells (MD-SCs) in vitro, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…RAD51-associated DNA repair in response to radiation has been studied in normal human Schwann cells and merlin-deficient Schwann cells (MDSC). In a recent in vitro investigation by Cohen et al, human MDSCs exhibited high levels of g-H2AX 6 h after exposure to 6, 12, and 18 Gy of single fraction radiation (18). Although the levels of g-H2AX were similar across the three radiation groups, MDSCs demonstrated a dose-dependent loss in cell viability at 96 h. The authors show that a lower dose of radiation (i.e., 6 Gy), MDSCs can initiate a robust RAD51 DNA repair response to evade cell loss.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…RAD51-associated DNA repair in response to radiation has been studied in normal human Schwann cells and merlin-deficient Schwann cells (MDSC). In a recent in vitro investigation by Cohen et al, human MDSCs exhibited high levels of g-H2AX 6 h after exposure to 6, 12, and 18 Gy of single fraction radiation (18). Although the levels of g-H2AX were similar across the three radiation groups, MDSCs demonstrated a dose-dependent loss in cell viability at 96 h. The authors show that a lower dose of radiation (i.e., 6 Gy), MDSCs can initiate a robust RAD51 DNA repair response to evade cell loss.…”
Section: Discussionmentioning
confidence: 94%
“…A recent in vitro study showed that merlin-deficient Schwann cells (MD-SCs) displayed upregulation of the DNA repair protein RAD51 in response to IR-induced DNA damage when compared to normal human Schwann cells (18). However, little is known about the activity of RAD51 in response to radiation-induced DSBs in VS.…”
mentioning
confidence: 99%
“…Other tumors can evade radiation injury by upregulating DNA repair proteins, such as RAD51, DNA-PK [ 160 , 165 ], RPA1 [ 166 ], LIG4 [ 167 ], HIF-1 [ 168 ], HDAC [ 169 ], Wee1 [ 170 ], CDK1 [ 171 ], and Chk1 [ 160 , 165 , 172 , 173 , 174 ]. In an in vitro study using normal human Schwann cells and merlin-deficient Schwann cells (MD-SCs), MD-SCs produced a robust RAD51 response when exposed to 6 Gy of radiation when compared to normal Schwann cells [ 175 ]. These findings suggest a possible mechanism of radiation resistance in schwannomas that warrants further investigation.…”
Section: General Mechanisms Of Radiation Resistancementioning
confidence: 99%
“…Although the molecular mechanisms for why faster-growing tumors would be less responsive to radiation are unknown, it was proposed that fast-growing tumors may be more radioresistant because they have efficient DNA repair mechanisms [ 30 ]. In an in vitro study, Cohen et al found that MD-SCs had a more robust upregulation of DNA repair protein RAD51 after exposure to 6 Gy of radiation than normal Schwann cells, suggesting that VS may upregulate DNA repair mechanisms in order to resist radiation injury [ 175 ]. However, at higher doses of radiation (12 and 18 Gy single fraction), merlin-deficient Schwann cells did not activate RAD51 more than baseline, suggesting that higher doses of radiation may be required to prevent activation of DNA repair proteins.…”
Section: Radiobiology and Radiation Resistance In Vestibular Schwannomamentioning
confidence: 99%